Geospatial Dynamics of Agriculture, Dietary Preferences, and Nutritional Wellness in the Panchganga Basin (International Journal of Food and Nutritional Sciences, 2021)
This research delves into the intricate interplay between geospatial dynamics of agriculture,dietary preferences, and nutritional wellness in the Panchganga Basin. Recognizing the vitalimplications for public health and regional development, the study aims to unravel the connectionsbetween land use patterns, crop distribution, and the nutritional habits of the population